Construction and validation of a low-cost system for indoor air quality measurements in livestock facilities - Delgado, Leonardo (2022)
In recent years, there has been an increase in demand for food of ani-mal origin. The number of intensive production systems such as pig and poultry farming has been increasing more and more and exerting great impacts on the environment, due to a large amount of particulate material and gaseous pollutants that are generated within these facilities. Thus, low-cost devices emerge as a cheap alternative that provides farmers with information on indoor air quality in its facilities. However, it is important that these devices make precise and accu-rate measurements, providing reliable concentration readings. Therefore, the ob-jective of this study is the construction and validation of a low-cost system capa-ble of measuring, storing and sending, via the mobile network, the concentrations of hydrogen sulfide, ammonia, carbon dioxide, PM2.5, PM10, temperature, and relative humidity. Preliminary inter-comparison tests showed that the built sys-tem had a reliable behavior in relation to all variables, even though the CO2 sen-sor was the one with the highest determination coefficient. The built device is able to provide continuous monitoring of atmospheric pollutants concentrations, at low cost and with simple handling.